Experimental Study on Engineering Properties of Cement Concrete Reinforced with Nylon and Jute Fibers - Naraindas Bheel; T. Tafsirojjaman; Yue Liu; Paul Awoyera; Aneel Kumar; Manthar Ali Keerio (Buildings, 2021)
The use of synthetic fiber and natural fiber for concrete production has been continuously investigated. Most of the materials have become popular for their higher flexibility, durability, and strength. However, the current study explores the engineering properties of cement concrete reinforced with nylon and jute fibers together. Varying proportions and lengths of nylon and jute fibers were utilized in the concrete mixture. Hence, the combined effects of nylon and jute fibers on workability, density, water absorption, compressive, tensile, flexural strength, and drying shrinkage of concrete were investigated. Results showed that concrete with 1% of nylon and jute fibers together by the volume fraction showed a maximum enhancement of the compressive strength, split tensile strength, and flexural strength by 11.71%, 14.10%, and 11.04%, respectively, compared to the control mix of concrete at 90 days. However, the water absorption of concrete increased with increasing nylon and jute fiber contents. The drying shrinkage of concrete decreased with the addition of nylon and jute fibers together after 90 days. Thus, the sparing application of both nylon and jute fiber as discussed in this study can be adopted for concrete production.